2021
DOI: 10.3390/cancers13174290
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Antitumor Compound HCA Promotes Glioma Cell Death by Inducing Endoplasmic Reticulum Stress and Autophagy

Abstract: Glioblastoma (GBM) is the most common and aggressive type of primary brain tumor in adults, and the median survival of patients with GBM is 14.5 months. Melitherapy is an innovative therapeutic approach to treat different diseases, including cancer, and it is based on the regulation of cell membrane composition and structure, which modulates relevant signal pathways. Here, we have tested the effects of 2-hydroxycervonic acid (HCA) on GBM cells and xenograft tumors. HCA was taken up by cells and it compromised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…During these experiments none of the mice lost more than 10% of their body weight (data not shown), and the oral administration of HCA was well tolerated. Indeed, HCA had been seen not to produce any toxicity in mice in earlier studies at studied doses [ 11 , 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During these experiments none of the mice lost more than 10% of their body weight (data not shown), and the oral administration of HCA was well tolerated. Indeed, HCA had been seen not to produce any toxicity in mice in earlier studies at studied doses [ 11 , 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies observed that HCA activated ER/UPR stress signaling pathways in glioma cells [ 11 ]. Since RE/UPR stress can trigger cell death, key proteins were studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we did not observe a therapeutic effect of cisplatin in the resistant PC-9 cell line lung tumor model xenograft in TCAM or in mouse ( Figure 3 ). Moreover, we demonstrated, through the U118MG GBM cell line described to be poorly responsive to TMZ in the mouse xenograft model [ 54 ], that TMZ induced tumor reduction in both mouse and TCAM models with a similar tumor growth inhibition pattern ( Figure 3 ). Thus, the TCAM might represent an interesting alternative to murine models in order to decipher drug resistance [ 18 ].…”
Section: Discussionmentioning
confidence: 96%